Nitrogen and phosphate metabolism in ectomycorrhizas. Issue 4 (11th June 2018) - Nehls, Uwe; Plassard, Claude
Abstract :         Summary 1047 I. Introduction 1047 II. Mobilization of soil N/P by ECM fungi 1048 III. N/P uptake 1048 IV. N/P assimilation 1049 V. N/P storage and remobilization 1049 VI. Hyphal N/P efflux at the plant–fungus interface 1052 VII. Conclusion and research needs 1054   Acknowledgements 1055   References 1055 Summary: Nutrient homeostasis is essential for fungal cells and thus tightly adapted to the local demand in a mycelium with hyphal specialization. Based on selected ectomycorrhizal (ECM) fungal models, we outlined current concepts of nitrogen and phosphate nutrition and their limitations, and included knowledge from Baker's yeast when major gaps had to be filled. We covered the entire pathway from nutrient mobilization, import and local storage, distribution within the mycelium and export at the plant–fungus interface. Even when nutrient import and assimilation were broad issues for ECM fungi, we focused mainly on nitrate and organic phosphorus uptake, as other nitrogen/phosphorus (N/P) sources have been covered by recent reviews. Vacuolar N/P storage and mobilization represented another focus point of this review. Vacuoles are integrated into cellular homeostasis and central for an ECM mycelium at two locations: soil‐growing hyphae and hyphae of the plant–fungus interface. Vacuoles are also involved in long‐distance transport. We further discussed potential mechanisms of bidirectional long‐distance nutrient transport (distances from millimetres to metres). A final focus of the review was N/P export at the plant–fungus interface, where we compared potential efflux mechanisms and pathways, and discussed their prerequisites.